2020
DOI: 10.1093/jscr/rjz389
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of a trigeminal artery associated with a posterior meningeal artery aneurysm: case report and literature review

Abstract: A 59-year-old female presented with severe headache and trouble of consciousness. The CT showed a subarachnoid hemorrhage FISHER IV with a hematoma of the right cerebellum. The angiography discovered a persistent left trigeminal artery associated with an aneurysm of the right posterior meningeal artery. The attempt of embolization failed and the patient suffered cerebral vasospasm and died. The persistence of a trigeminal artery is found in 0.1–0.6% of the population. It is the most frequent embryological caro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The presence of intracranial aneurysms in PTA patients not only increased the risk of cerebral hemorrhage, but also made it very easy for surgeons to cause serious intraoperative hemorrhage if the presence of this variant was not detected preoperatively. Bechri et al ( 32 ) reported that due to the thin vascular wall of PTA, aneurysm rupture was occur in the blood pressure of the internal carotid artery and basilar artery, which leaded causes cerebral hemorrhage. Yilmaz et al ( 33 ) also found that PTA patsients often produced aneurysms in the cavernous sinus, which could not only caused dizziness and headache due to the space occupying effect, but also produced symptoms of intracranial nerve paralysis due to compression of the trigeminal nerve.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of intracranial aneurysms in PTA patients not only increased the risk of cerebral hemorrhage, but also made it very easy for surgeons to cause serious intraoperative hemorrhage if the presence of this variant was not detected preoperatively. Bechri et al ( 32 ) reported that due to the thin vascular wall of PTA, aneurysm rupture was occur in the blood pressure of the internal carotid artery and basilar artery, which leaded causes cerebral hemorrhage. Yilmaz et al ( 33 ) also found that PTA patsients often produced aneurysms in the cavernous sinus, which could not only caused dizziness and headache due to the space occupying effect, but also produced symptoms of intracranial nerve paralysis due to compression of the trigeminal nerve.…”
Section: Discussionmentioning
confidence: 99%
“…Behari described an aneurysm on the posterior communicating artery, Maeshima showed a case of PTA connected with multiple aneurysms on ACA and MCA [8,28]. Bechri in 2020 reported a case of a posterior meningeal artery aneurysm coexisting with PTA [7]. In a great number of cases the persistent trigeminal artery is an incidental discovery and its clinical significance has been debated.…”
Section: Discussionmentioning
confidence: 99%
“…The reported incidence of the PTA ranges from 0.1 to 0.6% [7,24]. Most cases are detected incidentally during brain imaging performed for unrelated reasons, so the real frequency can be higher, based on unrecognized cases.…”
Section: Introductionmentioning
confidence: 99%